2013
DOI: 10.1111/trf.12080
|View full text |Cite
|
Sign up to set email alerts
|

Storage of red blood cells affects membrane composition, microvesiculation, and in vitro quality

Abstract: Significant changes to the RBC membrane occur during storage. The length of storage will influence RMP generation, osmotic fragility, hemolysis, and changes in deformability. These changes in RBC in vitro quality may contribute to transfusion reactions and negative posttransfusion outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
135
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(153 citation statements)
references
References 53 publications
15
135
1
2
Order By: Relevance
“…The same group of investigators recently revealed a near doubling in the absolute number of RBC-derived MV 42 days of storage [43]. Nevertheless, the role of MVs in TRALI development is yet to be elucidated.…”
Section: Microvesiclesmentioning
confidence: 93%
See 2 more Smart Citations
“…The same group of investigators recently revealed a near doubling in the absolute number of RBC-derived MV 42 days of storage [43]. Nevertheless, the role of MVs in TRALI development is yet to be elucidated.…”
Section: Microvesiclesmentioning
confidence: 93%
“…Almizraq et al [43] have recently shown that the MV released from RBC membranes is rich in polyunsaturated phospholipids [44]. In a comparative analysis of the lipid composition of MV and RBC membranes during storage showed that the glycerophospherine (PS) profile of stored RBC membranes did not resemble the PS profile of fresh RBCs, and the MV showed greater PS abundance [44].…”
Section: Microvesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that RBC MCHC and MCV change during blood storage and the type and extent of the changes depend on the additive preservation solution that is used to store the RBCs [21,23,24]. Therefore, in our simulations, RBC MCHC was varied from 14 to 22 mM and the volume of RBC was decreased from 90 to 60 mm 3 .…”
Section: Examined Effects Of Rbc Mchc MCV and Permeabilitymentioning
confidence: 99%
“…Numerous studies have found that the geometry of the red blood cell tends to become more spherical during storage thereby having a smaller surface area to volume ratio [10,[18][19][20]. The mean corpuscular hemoglobin concentration decreases, and the structure of RBC membrane changes significantly during storage [21,22]. In addition, RBC volume varies during blood storage but the type of change depends on which additive preservation solutions is used [23,24].…”
Section: Introductionmentioning
confidence: 99%